Criminal Sanction Policy in Law No. 8 of 1999 on Consumer Protection - Siti Nur Aisyiah; Emmilia Rusdiana (Universitas Negeri Surabaya, 2024)
Consumer protection is regulated in Law No. 8 of 1999 concerning Consumer Protection, hereinafter referred to as UUPK, this law aims to guarantee legal certainty to provide protection to consumers. It regulates sanctions, including criminal sanctions contained in Article 61 to Article 63. These criminal sanctions are considered imperfect because they should focus more on consumer protection and recovery of losses than criminal prosecution of business actors and are more oriented towards repair and recovery so that they can be more effective in repair losses suffered by consumers. These sanctions are also still not in accordance with the goals of reform in the politics of criminal law. This research aims to be able to optimize the goals in realizing order and justice through law enforcement and provide information regarding the accuracy of the formulation and implementation of criminal law in relation to the purpose of drafting the UUPK. This study aims to analyze legislation in the field of consumer protection associated with the formulation and implementation of criminal law. The research method used in this research is normative juridical research, using a statutory approach (statute approach) and a conceptual approach (conceptual approach). The legal materials used are primary and secondary legal materials. The analysis technique used in this study uses prescriptive analysis techniques. The results of the discussion prove that the formulation and implementation of criminal law in violations in the field of consumer protection shows that the principle of reasonable loss that can be described by the criminal act is not met, the principle of subsidiarity that criminal law is only ultimum remidium), the principle of proportionality in the form of a balance between losses and the purpose of punishment. the principle of legality in the principles of lex certa and lex stricta, and the principle of their practical use and effectiveness related to their enforcement, while the principle that is fulfilled is the principle of tolerance towards the formulation of criminal acts.